'Getting Rich Is Glorious':Environmental Values in the People's Republic of China. (1st May 2004) - Harris, Paul G.
Abstract : Pollution and overuse of resources in China have profound implications for the Chinese people and the world. Globalisation may be partly to blame for this situation, but it is hardly the only explanation. China has been overusing its resources for centuries. Traditional values appear to offer environmentally benign guidance for China's economic development, but they are largely impotent in the face of now-pervasive values manifested in Western-style consumption. Government policies go some way toward addressing this problem, but what may be required is a new set of values that brings self-interest and environmental protection into common cause.